2011
DOI: 10.1073/pnas.1017474108
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-II inhibition and soft 2D matrix maximize multinucleation and cellular projections typical of platelet-producing megakaryocytes

Abstract: Cell division, membrane rigidity, and strong adhesion to a rigid matrix are all promoted by myosin-II, and so multinucleated cells with distended membranes-typical of megakaryocytes (MKs)-seem predictable for low myosin activity in cells on soft matrices. Paradoxically, myosin mutations lead to defects in MKs and platelets. Here, reversible inhibition of myosin-II is sustained over several cell cycles to produce 3-to 10-fold increases in polyploid MK and a number of other cell types. Even brief inhibition gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
84
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 35 publications
10
84
0
Order By: Relevance
“…Collectively, these results demonstrated that MYH10 was involved in the switch from mitosis to endomitosis. This result is in agreement with previous results that have shown that MYH10 is involved in cytokinesis and that its knockdown in cell lines leads to multinucleated polyploid cells 15,20,21 .…”
Section: Myh10 Is Involved In the Switch From Mitosis To Endomitosissupporting
confidence: 94%
See 2 more Smart Citations
“…Collectively, these results demonstrated that MYH10 was involved in the switch from mitosis to endomitosis. This result is in agreement with previous results that have shown that MYH10 is involved in cytokinesis and that its knockdown in cell lines leads to multinucleated polyploid cells 15,20,21 .…”
Section: Myh10 Is Involved In the Switch From Mitosis To Endomitosissupporting
confidence: 94%
“…However, MYH10 silencing does not explain the entire polyploidization process. MYH10 silencing has a central role at the 2N-4N transition in MK by inducing failure of cytokinesis as also observed in MYH10-ablated cardiac myocytes 21 or COS cells 15,20 . However, MKs are not subsequently blocked in 4N.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Additional related studies have emphasized the critical role of hydrogel stiffness in skeletal muscle stem cell self-renewal 12 , neural stem cell behavior 13 and megakaryocyte poiesis 14 . 3D mechanical properties are similarly important in controlling adult stem cell fate in alginate hydrogels incorporating adhesive ligands 4 .…”
Section: Static Hydrogels That Mimic Biophysical Cuesmentioning
confidence: 99%
“…This results in yields of 10 122 PLTs per CD34 1 cord blood-derived or embryonic stem cell-derived MK, 18 which are themselves of limited availability, constituting a significant bottleneck in the ex vivo production of a PLT transfusion unit. Although second-generation cell culture approaches have provided further insight into the physiological drivers of PLT release, they have been unable to recreate the entire BM microenvironment, exhibiting limited individual control of extracellular matrix (ECM) composition, 19,20 BM stiffness, 21 endothelial cell contacts, 22,23 and vascular shear stresses, 24,25 and have been unsuccessful in synchronizing proPLT production, resulting in nonuniform PLT release over a period of 6 to 8 days. 26 Moreover, the inability to reproduce the BM microenvironment ex vivo, and resolve physiological proPLT extension and release by high-resolution live-cell microscopy, has significantly hampered efforts to study the cytoskeletal and signaling mechanics of PLT production.…”
Section: Introductionmentioning
confidence: 99%